Intelligent energy management system of series hybrid electric vehicle (HEV) - Khor, Ai Chia; Saiful Hakim, Che Mood @Mahyiddin; Mohamed, Mohd Rusllim (2018)
Regardless of chosen/preferred configurations, energy management system has become a vital functionality for hybrid electric vehicles (HEVs) to operate at an optimum or quasi-optimum to conserve energy with no impact on system performance. This study presents a design and testing through software and hardware simulation of a fuzzy logic energy management system for series hybrid electric vehicle. Fuzzy logic rule-based controller is used to manage the propulsion and power split between the engine, generator and energy storage depending on the vehicle energy demand. The system is capable to demonstrate the performance of a series hybrid electric vehicle under difference condition of operation with respect to speed and state of charge (SOC) for the battery pack.